Co-encapsulation of isoniazid and rifampicin in liposomes and characterization of liposomes by derivative spectroscopy - (:unkn) unknown (ELSEVIER, 2004)
Taking into consideration the benefits of the combined therapy of isoniazid (INH) and rifampicin (RIF), this study focused on co-encapsulation of INH and RIF in the same liposome formulation. INH was incorporated in the aqueous phase and RIF in the lipid layer. Liposomes containing either INH or RIF were also prepared. All liposome formulations were compared for their loading capacity, encapsulation percentage and release properties Drug amounts in the liposomes were estimated using peak-to-peak first-order derivative UV spectroscopy. Among the liposome formulations DPPC:chol liposomes showed the highest loading capacity (106.70 +/- 0.12 for INH and 18.17 +/- 0.06 (x 10(-3)) for RIF) and encapsulation percentage (73.84 +/- 0.78 for INH and 81.53 +/- 2.06 for RIF) compared to EPC:chol liposomes (loading capacity 93.36 +/- 0.58 for INH and 17.87 +/- 0.11 (x 10(-3)) for RIF; encapsulation percentage 64.61 +/- 0.51 for INH and 74.45 +/- 0.48 for RIF). Co-encapsulation of INH and RIF increased their individual encapsulation percentage and extended drug release compared to the formulations containing drug alone (Table 2). Results of this study support the conclusion that lipid and water soluble drugs can be successfully co-encapsulated in the same liposome formulation and also show that derivative UV spectroscopy is a sensitive method for direct and accurate quantification of these co-encapsulated drugs. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: isoniazid; rifampicin; liposome; drug co-encapsulation in liposomes; drug release; derivative spectrophotometry